1 2 2

:

  1. #1

    Jul 2012
    5,302

    :-
    1) 2
    7
    :-
    = +
    = 2 , = 7
    = 2 + 7
    2 - + 7 = 0

    2) 1/2 ( 3 , 2 )
    :-
    - 1 = ( - 1 )
    - 2 = 1/2 ( - 3 )
    2 - 4 = - 3
    - 2 + 1 = 0

    3)
    - 1/3 ( 1 , 2 )
    :-
    = +
    2 = - 1/3 1 +
    = 2 + 1/3 = 7/3
    = 7 /3

    4) 3 + 2 = 0
    :-
    = - /
    = - 3/2

    :-

    - 1

    = 1/ 2 + 2

    :-

    = 1 / 2



    = - 1

    = 1 / 2 - 1

    __________________

    :-

    3 + 2 + 6 = 0

    ( 6 , 2 )

    :-

    3 + 2 + 6 = 0

    3 = - 2 - 6

    = - 2 / 3 - 2

    = - 2 / 3

    = - +

    ( 6 , 2 )

    2 = - 2 / 3 6 +

    2 = - 4 + ................. = 6

    = - 2 / 3 + 6

    __________________

    :-

    = + = 3 + 2

    ( 1 , 2 ) ,

    :-

    = +

    = 3 + 2

    =

    = 3


    ( 1 , 2 ) 1

    = 3 + ............... ( 1 . 2 )

    2 = 3 1 +

    = 2 - 3 .......................... = - 1

    = 3 , = - 1

    __________________











  2. #2
      Eiman
    Jul 2011
    -
    14,750

    :

    .......

: 1 (0 1 )